B209 Fluroscopy and ultrasound guided erector spinae plane block for postoperative analgesia in lumbar spine fusion: a case report. (11th August 2022) - Moyano Acevedo, JR; Suarez, AM; Santoyo Barco, MF
Abstract : Background and Aims: The erector spinae plane (ESP) block is a regional technique associated with a multimodal approach that has shown a significant reduction in immediate postoperative pain and shorter hospital stay following lumbar spine surgery. Although it has been described as a technique of moderate or low complexity, several factors can make it difficult to use (lumbar approach, high body mass index, and anatomical abnormalities of the spine). This report describes the successful performance of a lumbar ESP after anticipating potential difficulties. Methods: Informed consent was obtained. A 68-year-old woman with height 150 cm, weight 80 kg, BMI 35.6, multilevel spinal stenosis, L6 transitional vertebrae (TV), and L5-L6 anterolisthesis, underwent decompression surgery and arthrodesis spanning interspaces L3-TV. After induction, in prone position, the surgeon performed a fluoroscopic marking of pedicles and transverse processes; then ESP was performed using the standard ultrasound technique (20 mL of 0.125% bupivacaine on both sides). Results: The patient reported mild to moderate incisional pain and oral feeding, assisted ambulation, and physical therapy within 12 hours. In the first 24 hours after surgery, mild pain was predominant. Opioid utilization was less than 10 milligrams of morphine in 24 hours. On the third post-operative day, she was discharged with assisted ambulation and satisfied with the analgesic plan. Conclusions: There are factors that could increase the level of difficulty in performing an ESP for lumbar fusion. Therefore, the anesthesiologist can accomplish it using fluoroscopic marking by the surgeon